Enhanced Oxidation of Organic Contaminants by Iron(II)-Activated Periodate: The Significance of High-Valent Iron–Oxo Species - Zong, Yang; Shao, Yufei; Zeng, Yunqiao; Shao, Binbin; Xu, Longqian; Zhao, Zhenyu; Liu, Wen; Wu, Deli (Environmental Science & Technology, 2021)
Potassium periodate (PI, KIO4) was readily activated by Fe(II) under acidic conditions, resulting in the enhanced abatement of organic contaminants in 2 min, with the decay ratios of the selected pollutants even outnumbered those in the Fe(II)/peroxymonosulfate and Fe(II)/peroxydisulfate processes under identical conditions. Both 18O isotope labeling techniques using methyl phenyl sulfoxide (PMSO) as the substrate and X-ray absorption near-edge structure spectroscopy provided conclusive evidences for the generation of high-valent iron–oxo species (Fe(IV)) in the Fe(II)/PI process. Density functional theory calculations determined that the reaction of Fe(II) with PI followed the formation of a hydrogen bonding complex between Fe(H2O)62+ and IO4(H2O)−, ligand exchange, and oxygen atom transfer, consequently generating Fe(IV) species. More interestingly, the unexpected detection of 18O-labeled hydroxylated PMSO not only favored the simultaneous generation of ·OH but also demonstrated that ·OH was indirectly produced through the self-decay of Fe(IV) to form H2O2 and the subsequent Fenton reaction. In addition, IO4– was not transformed into the undesired iodine species (i.e., HOI, I2, and I3–) but was converted to nontoxic iodate (IO3–). This study proposed an efficient and environmental friendly process for the rapid removal of emerging contaminants and enriched the understandings on the evolution mechanism of ·OH in Fe(IV)-mediated processes.